Competitive Immunoassays for the Detection of Small Molecules Using Single Molecule Arrays - Wang, Xu; Cohen, Limor; Wang, Jun; Walt, David R (Journal of the American Chemical Society, 2018)
Small-molecule detection is important for many applications including clinical diagnostics, drug discovery, and measurements of environmental samples and agricultural products. Current techniques for small-molecule detection suffer from various limitations including low analytical sensitivity and complex sample processing. Furthermore, as a result of their small size, small molecules are difficult to detect using an antibody pair in a traditional sandwich assay format. To overcome these limitations, we developed an ultrasensitive competitive immunoassay for small-molecule detection using Single Molecule Arrays (Simoa). We show that the competitive Simoa assay is approximately 50-fold more sensitive than the conventional ELISA. We performed theoretical calculations to determine the factors that influence the sensitivity of competitive Simoa assays and used them to achieve maximal sensitivity. We also demonstrate detection of small molecules in complex biological samples. We show that the competitive Simoa assay is a simple, fast, and highly sensitive approach for ultrasensitive detection of small molecules.